The Relationship between Academic Underachievement and Problematic Cell Phone Use among Medical Students - Saeideh Moslemizadeh; Habibeh Ahmadipour (Kerman University of Medical Sciences, 2021)
Background: Academic underachievement is a growing phenomenon among medical students, influenced by several factors.Objectives: This study investigated the relationship between academic underachievement and problematic cell phone use among medical students at Kerman University of Medical Sciences.Methods: This cross-sectional study was conducted on 300 medical students at KUMS during the academic year 2019. The Persian version of Problematic Cellular Phone Use Questionnaire was used for data collection. Also, the demographic data of the students were recorded, and they were asked to declare if they had a history of academic underachievement in the previous year. Data were analyzed by SPSS software version 20.0 using Chi-square test and logistic regression.Results: The mean age of medical students was 22.41±2.6 years, and the majority (74.3 %) of them were female. The chance of academic underachievement was 6.37 times higher in medical students who have problematic cellular phone use compared to those without it (OR=6.37, P=0.001). Also, this chance was 4.45 times higher in medical students who had a history of psychological disorders compared to those without (OR=4.45, P=0.02).Conclusion: The current study revealed that the chance of academic underachievement was higher in medical students with problematic cellular phone use and a history of psychological disorders. Given that academic underachievement is not uncommon, its related factors must be appropriately identified and intervened on time.